Teacher: can you see what i’m saying? a research experience with deaf learners (2011)
This paper reports a study carried out with eleven deaf volunteers who belonged to different academic programs at a Colombian public university but did not receive English instruction as part of their professional training. The main goal of the research study was to identify the effect of using Internet resources as support for the design and development of a blended English course for deaf university students. The data were collected by means of surveys, artifacts, logs and a recorded interview to understand what worked well for deaf students and what barriers could interfere with their English learning. The study revealed some insights into the learning process of deaf students and their preference for collaborative learning and tasks linked to visual media. Este artículo da cuenta de un estudio que se llevó a cabo con once voluntarios sordos, quienes pertenecían a diferentes programas académicos de una universidad pública colombiana, pero no recibían clases de inglés como parte de su formación profesional. El objetivo principal de la investigación fue identificar el efecto del uso de recursos de Internet como apoyo en el diseño y desarrollo de un curso híbrido (presencial y virtual) para estudiantes universitarios sordos. Los datos se recogieron por medio de encuestas, evidencias documentales, notas de campo y una entrevista grabada en video con el propósito de conocer qué funcionaba con los estudiantes sordos y qué obstáculos podían interferir con su aprendizaje del inglés. El estudio reveló algunas percepciones respecto al proceso de aprendizaje de los estudiantes sordos, su preferencia por el trabajo colaborativo y las actividades ligadas al medio visual.